Compact wide-band gysel power divider - Tekin, Harun; Savcı, Hüseyin Şerif; Elsherbeni, Atef Z. (Institute of Electrical and Electronics Engineers Inc., 2022)
A compact and wideband Gysel power divider is proposed in this study. The design steps on a widely available low-cost FR-4 substrate are presented. The design is simulated with a Method-of-Moments based 2.5D EM simulator and verified with measurement results. The power divider supports an operating bandwidth of 1.5 GHz between 1.94 GHz and 3.44 GHz. The measurements show an insertion loss of 4.5 dB and return loss better than 15 dB which agrees with simulations. The fabricated circuit has at least three-fold wider bandwidth (with %56 fractional bandwidth) and four-fold smaller size (3.6 cm x 4.3 cm) than similar designs in the recent literature.
Keywords: Compact; Gysel; Gysel Power Divider